Individual tree damage dominates mortality risk factors across six tropical forests. Issue 2 (20th November 2021) - Zuleta, Daniel; Arellano, Gabriel; Muller‐Landau, Helene C.; McMahon, Sean M.; Aguilar, Salomón; Bunyavejchewin, Sarayudh; Cárdenas, Dairon; Chang‐Yang, Chia‐Hao; Duque, Alvaro; Mitre, David; Nasardin, Musalmah; Pérez, Rolando; et al.
Summary: The relative importance of tree mortality risk factors remains unknown, especially in diverse tropical forests where species may vary widely in their responses to particular conditions. We present a new framework for quantifying the importance of mortality risk factors and apply it to compare 19 risks on 31 203 trees (1977 species) in 14 one‐year periods in six tropical forests. We defined a condition as a risk factor for a species if it was associated with at least a doubling of mortality rate in univariate analyses. For each risk, we estimated prevalence (frequency), lethality (difference in mortality between trees with and without the risk) and impact ('excess mortality' associated with the risk, relative to stand‐level mortality). The most impactful risk factors were light limitation and crown/trunk loss; the most prevalent were light limitation and small size; the most lethal were leaf damage and wounds. Modes of death (standing, broken and uprooted) had limited links with previous conditions and mortality risk factors. We provide the first ranking of importance of tree‐level mortality risk factors in tropical forests. Future research should focus on the links between these risks, their climatic drivers and the physiological processes to enable mechanistic predictions of future tree mortality.